2021
DOI: 10.1016/j.pedn.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Adherence in Hispanic Adolescents with Obesity or Type 2 Diabetes

Abstract: Purpose: Hispanic adolescents experience high rates of obesity and type 2 diabetes. The purpose of this study was to examine adherence to a 16-week personalized exercise intervention and the perception of family support for exercise, benefits and barriers to exercise and overall health in Hispanic adolescents diagnosed with obesity or type 2 diabetes. Design and methods: Using a secondary analysis of a larger feasibility trial, data from 21 Hispanic adolescents, 13 with T2D and 8 who were obese and 14 that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Seven articles ( Douthitt, 1994 ; Bruner and Spink, 2011 ; Birt et al, 2014 ; Alberga et al, 2019 ; Guerrero et al, 2020 ; Faulkner and Michaliszyn, 2021 ; Sunesson et al, 2021 ) were kept for review and related information is shown in Table 1 . The results summarized below were presented according to the purposes of the current review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven articles ( Douthitt, 1994 ; Bruner and Spink, 2011 ; Birt et al, 2014 ; Alberga et al, 2019 ; Guerrero et al, 2020 ; Faulkner and Michaliszyn, 2021 ; Sunesson et al, 2021 ) were kept for review and related information is shown in Table 1 . The results summarized below were presented according to the purposes of the current review.…”
Section: Resultsmentioning
confidence: 99%
“…The participants in the four studies were healthy children and adolescents ( Douthitt, 1994 ; Bruner and Spink, 2011 ; Alberga et al, 2019 ; Guerrero et al, 2020 ). Further, Faulkner’s study explored the children and adolescents with obesity and type 2 diabetes ( Faulkner and Michaliszyn, 2021 ). The qualitative studies all used semi structured interviews, with 19 healthy children and adolescents in Birt’s study and 14 children and adolescents with depression in Sunesson’s study ( Birt et al, 2014 ; Sunesson et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have addressed compliance with metabolic and biochemical targets, blood pressure, healthy diet, physical exercise, or therapeutic recommendations in retrospective and prospective cohorts of subjects with T2DM [ 27 30 ], there is little evidence of the physicians' opinions regarding adherence and difficulties for implementing recommendations of CPGs in clinical practice. Several factors have been noted to affect the implementation and adherence to diabetic guidelines, which can be categorized in different major groups, such as factors associated with intrinsic attributes of CPGs themselves, factors related to the implementation process, physician's and patient's related characteristics, and factors related to the organization of the healthcare system [ 24 ].…”
Section: Discussionmentioning
confidence: 99%